Characterizing the Mechanical Properties of Cementitious Emulsion Grout for Semi-Flexible Mixture - Jawad Fatima A. (EDP Sciences, 2021)
Grout is a cement-based material with high strength and workability that allowing it to be injected into small cracks or leaky areas. It is usually used to patch concrete cracks or holes, but it may also be used to fill voids under metal bases or digging anchors. Furthermore, grout is used efficiently in the production process of semi-flexible pavement mixtures. The purpose of this study is to characterize the effect of grout ingredients on their mechanical properties. The grout ingredients were Ordinary Portland Cement (OPC), silica fume (SF), emulsion (Em), super-plasticizer (SP), and water. Different proportions of mentioned materials were used to characterizing the developed grout through flowability, compressive strength, and flexural strength tests. Results showed that the flow time decrease with an increase in the W/B. Also, the compression strength of the grouts comprised OPC+EM reveals an optimal dosage: i.e., 20% EM. Moreover, SF generally leads to increase compressive and flexural strength. As the main conclusion, the mechanical properties of cementitious-emulsion grout are highly affected, but grout ingredient types, dosage, and properties.